Completely (iso-)split scale-invariant Coulomb branch geometries are isotrivial - Philip C. Argyres; Robert Moscrop; Souradeep Thakur; Mitch Weaver (Journal of High Energy Physics)
Abstract We show that scale-invariant special Kähler geometries whose generic r dim ℂ abelian variety fiber is isomorphic (completely split) or isogenous (completely iso-split) as a complex torus to the product of r one-dimensional complex tori have constant τ ij modulus on the Coulomb branch, i.e. are isotrivial. These simple results are useful in organizing the classification of scale-invariant special Kähler geometries, which, in turn, is relevant to the classification of possible 4-dimensional N $$ \mathcal{N} $$ = 2 supersymmetric superconformal field theories.